2021
DOI: 10.1016/j.ihj.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties to enter the left ventricle during percutaneous transvenous mitral commissurotomy (PTMC)- our experiences of 80 cases with modified techniques

Abstract: Background Percutaneous transvenous mitral commissurotomy (PTMC) is the standard of treatment for symptomatic severe rheumatic mitral stenosis (MS). PTMC has the standard Inoue technique, but we have to modify the procedure in many technically challenging cases, especially to cross the mitral valve. Methodology Two over-the-wire strategies to enter the LV were taken in 80 complex cases of PTMC. The first one was done by exchanging the J-shaped wire from the balloon, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was found that PTMC was not only a safe and effective surgery but also greatly improved patients' QOL, underscoring the significance of providing this procedure at an earlier stage of the disease. According to a local study done in 2019 at the Combined Military Hospital in Pakistan, the authors did not notice any post-PTMC problems such localized hematoma, mitral regurgitation, or circulatory compromise [16][17] . The patients' success rate with PTMC (mean age, 40.3 ±2.8) was very high.…”
Section: Discussionmentioning
confidence: 95%
“…It was found that PTMC was not only a safe and effective surgery but also greatly improved patients' QOL, underscoring the significance of providing this procedure at an earlier stage of the disease. According to a local study done in 2019 at the Combined Military Hospital in Pakistan, the authors did not notice any post-PTMC problems such localized hematoma, mitral regurgitation, or circulatory compromise [16][17] . The patients' success rate with PTMC (mean age, 40.3 ±2.8) was very high.…”
Section: Discussionmentioning
confidence: 95%